Asymmetric adjustment of inventory investment: aggregate data evidence from China. Issue 2 (15th April 2022) - Long, Shaobo; Ding, Lu; Ran, Rong
Abstract: Based on China's monthly data from January 2006 to June 2018, this paper uses the symmetric regressive distributed lag model (ARDL) and nonlinear asymmetric regressive distributed lag model (NARDL) to examine the impact of the real interest rate, products' shortage costs and products' selling prices on China's overall inventory investment, and focuses on the asymmetric impact of the three factors on inventory investment. The empirical results show that the real interest rate has a negative impact on inventory investment, and its inhibition effect is stronger than the pulling effect. The products' shortage costs have the positive effect on inventory investment, and the effect of increasing shortage costs are greater than that of decreasing the shortage costs. The products' selling prices are also positively correlated with inventory investment, but the decline of the products' selling prices has the greater impact than the increase of the products' selling prices.